2021
DOI: 10.1371/journal.pone.0246226
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 knowledge, attitudes, and practices of United Arab Emirates medical and health sciences students: A cross sectional study

Abstract: The COVID-19 pandemic is the largest viral pandemic of the 21st century. We aimed to study COVID-19 knowledge, attitudes, and practices (KAP) among medical and health sciences students in the United Arab Emirates (UAE). We performed a cross-sectional study between 2 June and 19 August 2020. The survey was distributed online using Survey Monkey. It was conducted in English and comprised two parts: socio-demographic characteristics, and KAP towards COVID-19. 712 responses to the questionnaire were collected. 90%… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 34 publications
6
29
0
1
Order By: Relevance
“…This also consistent with similar demographics of participants of surveys collected via online platforms [ 14 ]. Similar to our results reported that 86.0% of medical and health sciences students and 80.6% of the university students in UAE were females [ 15 , 16 ]. This study demonstrated that UAE population and residents have a good to excellent knowledge about COVID-19 and were aware of right practices to avoid the infection and its spread.…”
Section: Discussionsupporting
confidence: 91%
“…This also consistent with similar demographics of participants of surveys collected via online platforms [ 14 ]. Similar to our results reported that 86.0% of medical and health sciences students and 80.6% of the university students in UAE were females [ 15 , 16 ]. This study demonstrated that UAE population and residents have a good to excellent knowledge about COVID-19 and were aware of right practices to avoid the infection and its spread.…”
Section: Discussionsupporting
confidence: 91%
“…The majority of other inhabitants surveyed in Bangladesh (98.7%), 71.2% of whom were students, wore face masks [ 37 ]. This was 99.5% in Vietnam [ 38 ] and 95.0% in the United Arab Emirates [ 39 ]. At the same time, only 62.8% of the medical students surveyed in Poland wore face masks [ 36 ], 71% in Pakistan [ 40 ], 69% in Congo [ 9 ], and 58.1% in Nigeria [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…An interesting aspect of the research is comparing the knowledge of students of particular faculties. In studies from Omam, India, and the Arab Emirates, the level of knowledge of medical students and students of health sciences was compared, showing a higher level of knowledge among medical students [14][15][16]. An interesting aspect of our study is comparing the knowledge test scores of the different health sciences faculties and finding that midwifery students possessed a higher level of knowledge than nursing and emergency medical services students.…”
Section: Discussionmentioning
confidence: 82%
“…Sixty percent (n = 407/677) of students did not attend family gatherings and did not visit shopping malls, cafes, industrial areas, hospitals, or COVID-19 facilities as part of their volunteer work. Ninety-seven percent of subjects (n = 655) took precautions when taking home deliveries, 94% (n = 637) washed their hands more frequently, and 95% (n = 643) wore face masks [16].…”
Section: Discussionmentioning
confidence: 99%